Muslim Female Healthcare Personnel Dress Code: A Proposed Guideline - S, Saidun; Akhmetova, E; Abd Rahman, A. Awang (IIUM Medical Journal Malaysia, 2020)
Introduction: The struggle of Muslim women to comply with Islamic teaching while working in the healthcare sector has been a long-standing issue. Following the case of a Muslim nurse who was allegedly fired for non-adherence to the short-sleeve uniform rule, the Malaysian Muslim Consumers Association highlighted the need for a uniform guideline to prevent similar instances. Yet, no guideline has been issued to date. Materials and Methods: This conceptual study employed library research method to gather relevant materials. Library research was able to retrieve guidelines from seven Muslim-minority countries but none from Muslim-majority countries. Document analysis of the materials gathered was undertaken. The different guidelines were compared, with special reference to awrah-related issues. Results: Several major issues that healthcare personnel dress code considers are the safety, health, cleanliness, and comfort for both patients and healthcare personnel. Islamic dressing requirement is not only in line with clinical practice but Islam also highly promotes maintenance of safety, health, cleanliness, and comfort. The widely adopted ‘bare below the elbows (BBE) policy is the only practice that may contradict Islamic rules. However, some healthcare institutions in Muslim-minority countries allow modifications of uniform rules on religious grounds; some of the modifications are not observed in Muslim-majority countries. When providing direct patient care that requires BBE, the use of disposable over-sleeves is a good alternative to adhere to both clinical and Islamic standards. Conclusion: Healthcare personnel dress code policy that is concordant to both clinical and Islamic standards is possible although it may require greater resources.